Challenges and Perspectives of Banks in Accepting Crypto as Collateral for Banking Transactions - Herliono, Anggun Angriani Putri; Junus, Nirwan (Universitas Negeri Gorontalo, 2025)
The rapid development of digital technology has led to the emergence of crypto assets as a new financial instrument that is starting to be considered as collateral for banking transactions in Indonesia. Although crypto has been recognized as a digital commodity that can be traded on futures exchanges, there are currently no specific regulations explicitly governing its use as collateral for bank loans. This study aims to analyze the legal aspects, practical challenges, and risk management faced by banks in accepting crypto as collateral. The research method used is a normative legal method with a statutory and conceptual approach, supported by a literature review and comparative analysis of international practices. The results show that although crypto meets the criteria for collateral from a civil law perspective, banks still face several significant challenges, such as high price volatility, digital security risks, and the lack of standard operating procedures related to the assessment and execution of crypto collateral. Therefore, banks tend to position crypto as additional collateral, rather than primary collateral, to minimize the risk of loss. This study recommends the need to establish a more comprehensive and adaptive legal framework, strengthen technological infrastructure, and improve digital financial literacy to support the safe and effective implementation of crypto as collateral. Thus, synergy between regulators, industry players, and the public is essential to create an inclusive and sustainable digital financial ecosystem in Indonesia.